Bourdieu, Hysteresis, and Shame: Spinal Cord Injury and the Gendered Habitus. (April 2018) - Barrett, Timothy
This article offers a consideration of the gendered emotion of "shame" within the context of the lived experiences of spinal cord injured men, using "found life histories" as a source material. Drawing upon the Bourdieusian concept of "hysteresis, " I theorize the emergence of a gendered disjuncture between incorporated expectations, values and assumptions, and the substantive enactments of masculinity socially available in the aftermath of spinal cord injury. Shame was often experienced within contexts characterized by "dangerous" social proximity to pathologized "others" (namely, disabled people and children) against which hegemonic masculinity is defined. I conclude the article by highlighting the particular limitations that Bourdieusian social theory can be used to identify in relation to individualized therapeutic interventions designed to encourage spinal cord injured men to adopt new understandings of masculinity.